2011
DOI: 10.1080/10942910903176576
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Wild Garlic on Color, Free Fatty Acids, and Chemical and Sensory Properties of Herby Pickled Cheese

Abstract: The effect of wild garlic herb (Allium sp.) on color, free fatty acids, chemical and sensorial properties of Herby-Pickled cheese were investigated during ripening. Analyses were carried out on 2, 30, 60, and 90 days of ripening. Increasing of herb level in cheese, L * and b * values of cheese were decreased but, a * values was increased. The color values of all cheese samples changed significantly during ripening. The increase in herb levels in cheese resulted in a significant increase in total free fatty aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 31 publications
6
22
0
Order By: Relevance
“…In contrast, the amounts of C8:0, C12:0, C16:0, and C16:1 fatty acids significantly increased during ripening, while the amount of C4:0 fatty acid significantly decreased ( p < .01). These results are consistent with those reported by Tarakci et al () who have found a reduction in the amount of C4:0 fatty acid during cheese ripening. However, the results of a study performed by Voigt et al () contradict those obtained in this study.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, the amounts of C8:0, C12:0, C16:0, and C16:1 fatty acids significantly increased during ripening, while the amount of C4:0 fatty acid significantly decreased ( p < .01). These results are consistent with those reported by Tarakci et al () who have found a reduction in the amount of C4:0 fatty acid during cheese ripening. However, the results of a study performed by Voigt et al () contradict those obtained in this study.…”
Section: Resultssupporting
confidence: 93%
“…To determine the composition of FFA the method introduced by Tarakci, Temiz, Aykut, and Turhan () was used. For this purpose, fat was extracted from 10 g of cheese using chloroform/methanol solution (2:1 v/v) and then homogenized using an Ultra Turrax homogenizer (Cat X120, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The procedure for fat extraction was in accordance with that described by Taracki, Temiz, Aykut, and Turhan (2011) and was as follows: up to 10 g of ground sample was added to 60 mL of chloroform:ethanol (2:1 mL:mL), which was stirred using an Ultra Turrax homogeniser for 3 min. Then 15 mL of 1 Â 10 À3 Mol L À1 solution of calcium chloride was added, followed by vigorous stirring for 30 s. The mixture was centrifuged (2000 Â g) for around 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…The increase in herb level from 0.0% to 1.5% resulted in a significant increase in total FFAs contents of cheeses. Although the caproic, capric, lauric, myristic, and palmitic acid levels of cheese were affected significantly by herb addition, stearic and oleic acid levels decreased (Tarakci et al. 2007).…”
Section: Proteolysis and Lipolysis Of Otlu Cheesementioning
confidence: 99%